2002
DOI: 10.1002/jms.314
|View full text |Cite
|
Sign up to set email alerts
|

Identification of methyl salicylate as the principal volatile component in the methanol extract of root bark of Securidaca longepedunculata Fers

Abstract: Securidaca longepedunculata Fers (Polygalaceae) is commonly used as a medicine in many parts of Africa and shows promise for protecting stored grain against insect pests. Analysis of a methanol extract of the root bark by gas chromatography linked to mass spectrometry (GC/MS) showed a major component accounting for over 90% of the volatile material. This was identified as methyl 2-hydroxybenzoate (methyl salicylate) by comparison of the GC retention times and mass spectrum with those of synthetic standards. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0
4

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 10 publications
4
31
0
4
Order By: Relevance
“…The volatile oil of the roots contains large amounts of methyl salicylate (Van Wyk et al, 2005). The report agrees with those of Jayasakara et al (2002) and Lognay et al (2000), which revealed that the major component (over 90%) of the volatile material from the root bark is methyl-2-hydroxybenzoate (methyl salicylate). Furthermore, securinine, presenegenin, 2-hydroxybenzoate esters such as methyl 2-hydroxy-6-methoxybenzoate and its benzyl analogue were also reported.…”
Section: Phytochemistrysupporting
confidence: 92%
See 1 more Smart Citation
“…The volatile oil of the roots contains large amounts of methyl salicylate (Van Wyk et al, 2005). The report agrees with those of Jayasakara et al (2002) and Lognay et al (2000), which revealed that the major component (over 90%) of the volatile material from the root bark is methyl-2-hydroxybenzoate (methyl salicylate). Furthermore, securinine, presenegenin, 2-hydroxybenzoate esters such as methyl 2-hydroxy-6-methoxybenzoate and its benzyl analogue were also reported.…”
Section: Phytochemistrysupporting
confidence: 92%
“…Fatty acids and Triacylglycerol 13-hydroxyoctadeca-cis-9-trans-11-dienoic acid, 11-hydroxyhexadeca-cis-7-trans-9-dienoic acid and 9-hydroxytetradeca-cis-5-trans-7-dienoic acid Jayasakara et al (2002, Lognay et al (2000 The aqueous root and ethanol extracts yielded alkaloids, cardiac glycosides, flavonoids, saponins, tannins, volatile oils, terpenoids and some steroids (Junaid et al, 2008;Haruna et al, 2013a;Auwal et al, 2012;Gbadamosi, 2012) while chloroform and ethanol extracts indicated flavonoids, saponins, coumarins, tannins and alkaloids (Adebayo and Osman, 2012). The ethyl acetate fraction of the root contained compounds such as 1,5-dihydroxy-3,4,6,7,8-pentamethoxyxanthone, 1,7-dihydroxyxanthone, 5-Ο-prenyl-1-hydroxy-2,3,6,7,8-pentamethoxyxathanthone, 2-hydroxy-1, 7-dimethoxyxanthone, β-sitosterol, 1,7-dihyroxy-4-methoxyxanthone, quercetin-3-O-β-galacto-pyranoside and 3-hydroxy-6-methoxysalicylic acid (Meli et al, 2007).…”
Section: Phytochemistrymentioning
confidence: 99%
“…As shown in Figure 3, methanol-soluble fraction contains a few sugars with glucose as major monosaccharide, while in methanol-insoluble fraction there are glucose and xylose which are detected in higher concentrations. On the other hand, the higher level of total phenol determined by spectrophotometry in methanol-soluble fraction (Table 2) was also confirmed by GC-MS analysis of silylated methanol-soluble fraction (See Figure S2 Supplementary Materials for GC-MS analysis), thus confirming the well-known affinity of polyphenols for methanol as solvent [23]. Thus, methanol-soluble fraction could be used for its antioxidant activity, which is usually correlated with total phenols content [24].…”
Section: Bark Extractives From Ethanol-water Pretreatmentsupporting
confidence: 60%
“…Phytochemical studies of the root and root bark has led to the isolation of a number of compounds. Some of these include beta-D-(3,4-disinapoyl)fructofuranosyl-alpha-D-(6-sinapoyl)glucopyranoside and beta-D-(3-sinapoyl)fructofuranosyl-alpha-D-(6-sinapoyl)glucopyranoside which are sucrose derivatives (De Tommasi et al, 1993), the alkaloids elymoclavine, and dehydroelymoclavine, an ergoline compound and cinnamonic acid (Wrobel et al, 1996), methyl 2-hydroxybenzoate (methylsalicylate), methyl 2-hydroxy-6-methoxybenzoate esters and its benzyl analogue (Jayasekara et al, 2002), flavonoids (Ajali and Chukwurah, 2004), and the xanthones: 1, 7-Dimethoxy-2-hydroxy-xanthone and 1, 4-dihydroxy-7-methoxy-xanthone (Rakuambo et al, 2004). Also, a number of fatty acids and triglycerols such as coriolic (13-hydroxyoctadeca-cis-9, trans-11-dienoic) acid, 11-hydroxyhexadeca-cis-7, trans-9-dienoic acid and 9-hydroxytetradecacis-5, trans-7-dienoic acid have been isolated from the seed oil of S. longipedunculata (Smith et al, 1979).…”
Section: Introductionmentioning
confidence: 99%